Block the Roads, Lock the Doors - Rahamzan, Nursyafizan Amalina Binti; Gopal, Nithya Renu; Yeng, Lou Wei (International Journal of Human and Health Sciences (IJHHS), 2021)
Pseudoaneurysm of the uterine arteries is a rare cause of secondary postpartum haemorrhage (PPH), following caesarean section or vaginal delivery. Whilst uterine artery embolization serves as an important and effective treatment for most cases of symptomatic uterine artery pseudoaneurysm, it is not without the risk of failing. Herein, we report a case of a near missed uterine artery pseudoaneurysm with nidus measuring about 1.7 x 2.7 x 2.8 cm. presenting as secondary postpartum haemorrhage 19 days post lower segment caesarean section, who underwent bilateral uterine arteries embolisation using Polyvinyl Alcohol (PVA) particles and gel foam until near stasis. Immediate check angiogram post uterine artery embolization (UAE) in our case reveals no residual pseudoaneurysm, however our patient had recurrent bleeding 2 days following the procedure. Repeated transabdominal ultrasound following recurrent bleeding showed similar size of colour doppler uptake at uterine fundus which indicates reperfusion of the pseudoaneurysm. Block the roads and lock the doors, the recurrent bleeding was managed successfully with prolonged Bakri Balloon tamponade. This case report was written with the objective of identifying the role of balloon tamponade as a method in the treatment of secondary PPH secondary to uterine arteries pseudoaneurysm. We also aim to show that with colour doppler ultrasounds as a basic imaging equipment in obstetric hospitals, we can spare the repercussion of a missed diagnosis of uterine artery pseudoaneurysm. Bakri Balloon used as uterine tamponade may be a treatment of choice with single lesion pseudoaneurysm which protrudes into the uterine cavity and not involving the lower segment of the uterus. Further studies however are needed to determine the size of pseudoaneurysm suitable for obliteration using prolonged balloon tamponade. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S6